Improvements in the modulus and strength of multi-dimensional hybrid composites through synergistic reinforcement between 1D fiber and 0D particle fillers - Markandan, Kalaimani (2022)
Alumina toughened zirconia (ATZ), aluminum (Al) and titanium (Ti) particulate fillers were added to carbon fiber-reinforced polycarbonate composites (PC–CF) at the percolation threshold (20 vol.%) to form a hybrid composite with multi-dimensional fillers. Experiments indicate that the storage modulus and yield strength were increased by a maximum of 148% and 8%, respectively. In contrast, mechanical properties of the composite deteriorated when additional 1-dimensional (1D) chopped carbon fibers were incorporated in any amount. Using the Hashin–Shtrikman and Suquet analysis to remove the influence of filler material property, it was shown that the stiffening and strengthening occurred because 0D particles could be dispersed in the interstitial sites of the PC–CF composite more easily than 1D fibers without causing significant agglomeration. Theoretical predictions from previous studies and electrical conductivity measurements support this premise. Employment of this novel strategy produced polycarbonate hybrid composites with specific strengths exceeding that of magnesium alloys, steel and some aluminum alloy grades, as well as combinations of strength and density not found in current engineering materials.